FEATURES OF EMOTIONAL DEVELOPMENT OF PRESCHOOL CHILDREN - Yulchiboyeva Dilfuza Ergashevna (Galaxy International Interdisciplinary Research Journal, 2022)
The article analyzes the psychological development of preschool children, their school preparation processes, and the difficulties they encounter in adapting to educational activities.